Production-Ready Decomposition of Series Resistance Into Lateral and Fixed Components - Clugston, Donald; Klöter, Bernhard (SiliconPV Conference Proceedings, 2025)
The series resistance (Rs) of a solar cell is commonly treated as a constant, but this is a very poor approximation: in modern cells, Rs can vary by a factor of 4 depending on illumination, bias voltage, and temperature. The naïve model leads to incorrect characterization of cell parameters and misattribution of cell losses. Wagner’s linear-response series resistance (LR-Rs) model attempts to treat Rs rigorously but experimental confirmation of the model is limited to EL and PL measurements. In this work we validate the LR-Rs model using IV measurements at multiple light intensities. We find a hyperbolic dependence of Rs on diode current as predicted by Wagner. The LR-Rs model fits the data extraordinarily well, but with a much higher geometric dependency than predicted by Wagner. We show that the model allows us to decompose series resistance into lateral and fixed components. This decomposition is now available in all WAVELABS commercial LED flashers. We illustrate the immediate benefits of this improved model in commissioning of a heterojunction production line.